Emerging applications and research trends of 3D printing and bioprinting in thoracic surgery: a bibliometric and visualized analysis - Kong, Demiao; Deng, Jingjing; Mao, Qikun; Zhao, Xun; Ye, Limin; Han, Liankui; Zhou, Jianfeng; Yang, Lin (Frontiers in Surgery, 2026)
BackgroundThree-dimensional (3D) printing and bioprinting technologies have rapidly evolved into essential tools in thoracic surgery, enabling personalized anatomical modeling, implant fabrication, and tissue engineering. However, the global research landscape and thematic evolution of this field remain incompletely characterized.MethodsA comprehensive bibliometric and visualized analysis was conducted using the Web of Science Core Collection, Scopus, and PubMed databases, covering studies published between 2008 and 2024. Data visualization and network analyses were performed using CiteSpace (v6.2.4R) and VOSviewer (v1.6.18) to assess publication trends, author and institutional collaborations, co-citation patterns, and keyword evolution.ResultsA total of 740 publications were identified, including 627 original articles and 113 reviews, contributed by 4,077 authors from 1,277 institutions across 71 countries. Annual publications increased steadily, peaking in 2024. China ranked first in publication volume (205 papers, 27.7%), while the United States had the highest citation impact (10,969 citations; 58.66 citations per paper). The most active journals were Journal of Thoracic Disease and Medical Physics. Keyword and co-citation analyses revealed three main research phases (1): anatomical modeling and surgical simulation (2008–2015) (2); prosthetic design and clinical application (2016–2020); and (3) tissue engineering, radiotherapy guidance, and bioprinting innovations (2021–2024). Emerging hotspots included electrospinning, volatile organic compound sensing, and tumor-specific implant customization.ConclusionGlobal research on 3D printing in thoracic surgery has expanded rapidly, with a clear transition from mechanical reconstruction toward biologically functional and regenerative approaches. The integration of bioprinting with advanced imaging, artificial intelligence, and robotics holds promise for personalized, precision thoracic surgery. Continued interdisciplinary collaboration will be essential to accelerate clinical translation and regulatory approval of biofabricated constructs.